2015
DOI: 10.1007/s10854-015-3183-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive nanocomposite adhesives based on epoxy or chloroprene containing polyaniline, and carbon nanotubes

Abstract: This study is focused on the preparation of electrically conductive nanocomposite adhesives based on epoxy resin or chloroprene rubber containing polyaniline, and multi-walled carbon nanotubes (MWCNTs). For this purpose, MWCNTs were carboxylated (MWCNTs-COOH) by conventional acid oxidation process, and then poly(ethylene glycol) monomethylether was covalently attached to the carboxylated MWCNTs via a esterification reaction. Moreover, carboxylic groups in the MWCNTs-COOH were reduced to alcohol groups (MWCNTs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Uniform dispersion of nanosized metal oxide in the polymer matrix introduces more conducting paths and that leads to higher conductivity. These results are in good agreement with recently reported work . It can be concluded that the fabricated PVCin/NiO nanocomposite exhibits remarkable electrical and magnetic properties, which may find application in various electromagnetic shielding, high‐frequency electric devices.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Uniform dispersion of nanosized metal oxide in the polymer matrix introduces more conducting paths and that leads to higher conductivity. These results are in good agreement with recently reported work . It can be concluded that the fabricated PVCin/NiO nanocomposite exhibits remarkable electrical and magnetic properties, which may find application in various electromagnetic shielding, high‐frequency electric devices.…”
Section: Resultssupporting
confidence: 92%
“…These results are in good agreement with recently reported work. 42 It can be concluded that the fabricated PVCin/NiO nanocomposite exhibits remarkable electrical and magnetic properties, which may find application in various electromagnetic shielding, high-frequency electric devices.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 96%
“…Both pristine HNTs and modified HNTs showed strong peaks at 3697 and 3615 cm −1 , respectively, which correspond to the stretching vibration of Al-OH groups in the inner surface; at 1028 and 909 cm −1 , peaks corresponded to Si-O stretching and Al-OH bending vibrations, respectively [57]. Meanwhile, minor peaks at 2932, 2359, 1680, and 1540 cm −1 , corresponding to C-H stretching vibration, carbonyl group [58], hydrogen bonding of COOH groups [59], N-H bending vibration [60], and C-N stretching vibration [61], respectively, could be seen in the gelatin-modified HNTs spectrum rather than in the spectrum of pristine HNTs.…”
Section: Characterization Of Nanofillersmentioning
confidence: 99%
“…Researchers also have used conductive fillers like carbon black, graphene nanoplatelets along with CNT so that they support the conductive network of each other, and thus, offer better conductivity . Few articles are also reported based on CNT and PANI hybrid filler system wherein CNT is proposed to form conductive bridges between sparse PANI particles, thereby, lowering the percolation threshold .…”
Section: Introductionmentioning
confidence: 99%